2003
DOI: 10.5194/acp-3-1633-2003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of impact of aviation on cirrus cloud formation

Abstract: Abstract. This work examines changes in cirrus cloud cover (CCC) in possible association with aviation activities at congested air corridors. The analysis is based on the latest version of the International Satellite Cloud Climatology Project D2 data set and covers the period 1984-1998. Over the studied areas, the effect of large-scale modes of natural climate variability such as ENSO, QBO and NAO as well as the possible influence of the tropopause variability, were first removed from the cloud data set in ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The mean ISCCP total cloud amount for this band is ,65%, while there is almost no trend in the cloud coverage. There are however trends in the amount of cloud types, as noted by Zerefos et al (2003) for cirrus clouds, which is presumably due to increasing air traffic. The trend in the GOME series is probably linked to the degradation of the instrument's solar diffuser -this affects the COT deviation (%) GOME cloud optical thickness monthly mean 14.48, trend −1.07% ISCCP cloud optical thickness monthly mean 9.04, trend +1.35% Figure 9.…”
Section: Global Mean Cloud Propertiesmentioning
confidence: 93%
“…The mean ISCCP total cloud amount for this band is ,65%, while there is almost no trend in the cloud coverage. There are however trends in the amount of cloud types, as noted by Zerefos et al (2003) for cirrus clouds, which is presumably due to increasing air traffic. The trend in the GOME series is probably linked to the degradation of the instrument's solar diffuser -this affects the COT deviation (%) GOME cloud optical thickness monthly mean 14.48, trend −1.07% ISCCP cloud optical thickness monthly mean 9.04, trend +1.35% Figure 9.…”
Section: Global Mean Cloud Propertiesmentioning
confidence: 93%
“…The coverage of aviation-induced cirrus is estimated to be 1.8 to 10 times higher than the one caused by contrails . According to Stordal et al (2005) cirrus coverage in Europe increased by 1-2% per decade, Zerefos et al (2003) find a value of 1.8% for Europe. The optical thickness of contrails on global average lies between 0.15 and 0.25 (Minnis et al, 2005), Meyer et al (2002) found a lower value of 0.1 for Europe.…”
Section: Introductionmentioning
confidence: 96%
“…The detection (measurement), properties, formation, evolution and radiative effects of linear-shaped contrails and/or the contrail-induced cloudiness have been subject to a large number of studies (Zerefos et al, 2003;Schumann, 2005;Stordal et al, 2005;Gao et al, 2006;Hong et al, 2008;Frömming et al, 2011). The physical mechanism behind its formation is now well understood; however, due to the uncertainties in the modeling of its occurrence and of its properties varying in time and space, the calculation of the related RF is still marked by a low to very-low level of scientific understanding .…”
Section: P Huszar Et Al: Modeling the Climate Impact Of Aviationmentioning
confidence: 99%